2021
DOI: 10.12688/wellcomeopenres.16559.1
|View full text |Cite
|
Sign up to set email alerts
|

In vivo negative regulation of SARS-CoV-2 receptor, ACE2, by interferons and its genetic control

Abstract: Background: Angiotensin I converting enzyme 2 (ACE2) is a receptor for the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and differences in its expression may affect susceptibility to infection. Methods: We performed a genome-wide expression quantitative trait loci (eQTL) analysis using hepatitis C virus-infected liver tissue from 190 individuals. Results: We discovered that polymorphism in a type III interferon gene (IFNL4), which eliminates IFN-λ4 production, is associated with a two-fold incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…However, data remains conflicting; indeed, ISGs expression is not influenced by the presence of rs11322783 ∆G allele in HIV-1 infected patients [28]. More recently, Azim Ansari et al found that expression of Angiotensin-converting enzyme 2 (ACE2), the functional receptor for SARS-CoV-2 entry into host target cells, is negatively correlated with IFNL4 production [29]. Remarkably, ACE2 transcripts' level (all isoforms) in vivo were correlated with those of ISG15, a marker of type I and III IFNs' activation in patients suffering from respiratory diseases not caused by SARS-CoV-2 [30].…”
Section: Introductionmentioning
confidence: 99%
“…However, data remains conflicting; indeed, ISGs expression is not influenced by the presence of rs11322783 ∆G allele in HIV-1 infected patients [28]. More recently, Azim Ansari et al found that expression of Angiotensin-converting enzyme 2 (ACE2), the functional receptor for SARS-CoV-2 entry into host target cells, is negatively correlated with IFNL4 production [29]. Remarkably, ACE2 transcripts' level (all isoforms) in vivo were correlated with those of ISG15, a marker of type I and III IFNs' activation in patients suffering from respiratory diseases not caused by SARS-CoV-2 [30].…”
Section: Introductionmentioning
confidence: 99%